Apoptosis modulators in the therapy of neurodegenerative diseases - Deigner, Hans-Peter; Haberkorn, Uwe; Kinscherf, Ralf (Expert opinion on investigational drugs, 2000)
Apoptosis is a prerequisite to model the developing nervous system. However, an increased rate of cell death in the adult nervous system underlies neurodegenerative disease and is a hallmark of multiple sclerosis (MS) Alzheimer’s- (AD), Parkinson- (PD), or Huntington’s disease (HD). Cell surface receptors (e.g., CD95/APO-1/Fas; TNF receptor) and their ligands (CD95-L; TNF) as well as evolutionarily conserved mechanisms involving proteases, mitochondrial factors (e.g., Bcl-2-related proteins, reactive oxygen species, mitochondrial membrane potential, opening of the permeability transition pore) or p53 participate in the modulation and execution of cell death. Effectors comprise oxidative stress, inflammatory processes, calcium toxicity and survival factor deficiency. Therapeutic agents are being developed to interfere with these events, thus conferring the potential to be neuroprotective. In this context, drugs with anti-oxidative properties, e.g., flupirtine, N-acetylcysteine, idebenone, melatonin, but also novel dopamine agonists (ropinirole and pramipexole) have been shown to protect neuronal cells from apoptosis and thus have been suggested for treating neurodegenerative disorders like AD or PD. Other agents like non-steroidal anti-inflammatory drugs (NSAIDs) partly inhibit cyclooxygenase (COX) expression, as well as having a positive influence on the clinical expression of AD. Distinct cytokines, growth factors and related drug candidates, e.g., nerve growth factor (NGF), or members of the transforming growth factor-β (TGF-β ) superfamily, like growth and differentiation factor 5 (GDF-5), are shown to protect tyrosine hydroxylase or dopaminergic neurones from apoptosis. Furthermore, peptidergic cerebrolysin has been found to support the survival of neurones in vitro and in vivo. Treatment with protease inhibitors are suggested as potential targets to prevent DNA fragmentation in dopaminergic neurones of PD patients. Finally, CRIB (cellular replacement by immunoisolatory biocapsule) is an auspicious gene therapeutical approach for human NGF secretion, which has been shown to protect cholinergic neurones from cell death when implanted in the brain. This review summarises and evaluates novel aspects of anti-apoptotic concepts and pharmacological intervention including gene therapeutical approaches currently being proposed or utilised to treat neurodegenerative diseases.